(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of high-risk preeclampsia and associated factors among pregnant women at 11-13 weeks and 6 days of gestation at Can Tho city Obstetrics and Gynecology Hospital. Methods: A cross-sectional analytical study was conducted on 1672 pregnant women undergoing preeclampsia screening at 11-13 weeks and 6 days of gestation at Can Tho city Obstetrics and Gynecology Hospital from November 2023 to April 2025. High-risk screening was performed using the PerkinElmer LifeCycle™ software (based on a Bayesian model), which has been validated by the Fetal Medicine Foundation for predicting the risk of preeclampsia. Logistic regression analysis was applied to identify factors associated with high-risk preeclampsia. Results: The prevalence of high-risk preeclampsia was 7.1%. Significant associated factors included: civil servant occupation (OR = 1.638; p = 0.017), education level ≤ high school (OR = 1.696; p = 0.035), and nulliparity (OR = 2.071; p = 0.001). The risk increased with BMI = 23-24.9 kg/m² (OR = 1.962; p = 0.006) and BMI ≥ 25 kg/m² (OR = 2.345; p < 0.001). Conclusions: The prevalence of high-risk preeclampsia among pregnant women at 11-13 weeks and 6 days of gestation was relatively high (7.1%). The main associated factors were BMI, nulliparity, and socio-demographic characteristics.